Decoupling the Effects of Atmospheric Humidity and Soil Moisture on Cereal Physiology - Dobrijevic, Daisy (2021)
Climate change is driving perturbations to global humidity levels with rises and falls already observed across many of the crop growing regions whilst drought continues to threaten agricultural productivity. Soil moisture content determines how much water can be supplied to a plant and atmospheric humidity influences vapour pressure deficit (VPD) thus driving transpirational demand. The influences of both this supply and demand on plant physiology are often overlooked, with drought study research seldom focused on the possible influences of humidity. This thesis aims to address this problem by decoupling the effects of humidity and soil moisture on maize (Zea mays) and wheat (Triticum aestivum cv. Paragon) through controlled growth under four treatments; high humidity high soil moisture, high humidity low soil moisture, low humidity high soil moisture, low humidity low soil moisture. This thesis found distinct differences in response between young maize and wheat crops with maize appearing more sensitive to humidity and wheat more to soil moisture. There was also variation between species in which areas of physiology were influenced most by the treatment conditions, as maize showed more responses related to biomass production and root architecture, whereas wheat gas exchange and stomatal morphology were more heavily impacted. This thesis highlights the importance of studying the effects of humidity and soil moisture concurrently as both maize and wheat were affected by individual treatments as well as significant interactions between the two. There is also evidence that high humidity could be mitigating some effects of low soil moisture conditions in the early growth of both species, which could have big impacts on future irrigation practices, commercial glasshouses, and predictive hydraulic and climatic models.